2016
DOI: 10.9767/bcrec.11.1.414.40-46
|View full text |Cite
|
Sign up to set email alerts
|

Visible Light Photocatalytic Properties of Modified Titanium Dioxide Nanoparticles via Aluminium Treatment

Abstract: Titanium dioxide (TiO2) has gained much attentions for the last few decades due to its remarkable performance in photocatalysis and some other related properties. However, its wide bandgap (~3.2 eV) can only absorb UV energy which is only ~5% of solar light spectrum. The objective of this research was to improve the photocatalytic activity of TiO2 by improving the optical absorption to the visible light range. Here, colored TiO2 nanoparticles range from light to dark grey were prepared via aluminium treatment … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
1
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(1 citation statement)
references
References 23 publications
0
1
0
Order By: Relevance
“…Another article in this issue was focused on visible light photocatalytic properties of modified titanium dioxide nanoparticles via aluminium treatment studied by Ariyanti et al [6]. They found that the modified TiO2 is able to absorb up to 50% of visible light (400-700 nm) and shows a relatively good photocatalytic activity in organic dye (Rhodamine B) degradation under visible light irradiation compared with the commercial TiO2.…”
mentioning
confidence: 99%
“…Another article in this issue was focused on visible light photocatalytic properties of modified titanium dioxide nanoparticles via aluminium treatment studied by Ariyanti et al [6]. They found that the modified TiO2 is able to absorb up to 50% of visible light (400-700 nm) and shows a relatively good photocatalytic activity in organic dye (Rhodamine B) degradation under visible light irradiation compared with the commercial TiO2.…”
mentioning
confidence: 99%